Laparoscopic Pyelolithotomy for the Management of Large Renal Stones with Intrarenal Pelvis Anatomy - Simforoosh, Nasser; Radfar, Mohammad Hadi; Valipour, Reza; Dadpour, Mehdi; Kashi, Amir Hossein (Urology Journal, 2020)
Purpose: The role of laparoscopic pyelolithotomy (LPL) in the management of renal stones is evolving. One of the challenges in LPL for renal stones is patients with intrarenal pelvis. Here we present our experience with laparoscopic pyelolithotomy for the management of renal stones with intrarenal pelvis anatomy. Materials and Methods: Patients candidate for laparoscopic pyelolithotomy from February 2014 to March 2015 were included. Intrarenal pelvis was defined as > 50% of the renal pelvis area contained inside renal parenchyma. Laparoscopic pyelolithotomy was done by transperitoneal approach. Residual stones were checked by computed tomography and/or intravenous pyelography and ultrasonography 6 weeks after the operation. Results: 28 patients were included in this study. The mean±SD of patients’ age was 45.8±12.5 years. 19 patients (68%) were male. Stone locations were pelvis, multiple, and staghorn in 22, 3, and 3 patients respectively. The mean±SD of operation duration was 160±48 minutes. Residual stones were observed in 3 patients with multiple (n=2) or staghorn (n=1) stones. Urinary leak was observed in 3 patients and was managed conservatively in 2 patients. In one patient ureteral stent was inserted by cystoscopy. No conversion to open surgery or re-operation occurred. Conclusion: Laparoscopic pyelolithotomy is a feasible operation for patients with renal stones and intrarenal pelvis in centers with adequate experience in laparoscopy. However, the success of LPL decreases in patients with multiple stones and intrarenal pelvis.